Fabrication of electro spinning 1D ZnO Nano fibers as UVPhotoconductor - Raad Sabry; Firas Mohammed; Roonak A.Alkareem (Engineering and Technology Journal, 2015)
The electrospinning technique was used to fabricate 1D nanofibers of Zinc Oxide (ZnO). Polyvinylpyrrolidone (PVP) ̸ zinc acetate Nano fibers electrospun using solution containing PVP dissolved in ethanol and zinc acetate in distilled water were mixed, followed by calcination at 500°C for 3hours to remove the polymer. XRD pattern show the hexagonal wurtzite structure of ZnO NFs without any impurities. FESEM pictures show a network of nanofibers with diameters less than 100 nm and several micrometers in length of ZnO, these nanostructures increase the ratio of surface area to volume and improve the physical properties of the materials. The Photoluminescence (PL) of the films was studied and the energy gap and the optical properties were estimated. A photoconductor device was constructed by electroding the films with silver conducting electrode (IDE) using screen print method, The result shown that the resistance of the nanofiber films decrease dramatically when exposes to UV light. In addition, the change of conductivity with the change of wavelengths was studied also the photoconductivity was examined under different bias voltage.